What Kind of Data do Government Agencies Have? - Carlson, Virginia (O'Reilly Media, Inc., 2011)
Data integration and viz technology have given rise to an appetite for government data-the Gov 2.0 movement. Do government agencies have good data? Sort of: I believe that an understanding of data limitations has gotten short shrift in the drive to develop the next app. I'll discuss why a knowledge of the complexities of government data is crucial to building quality decision-making tools.